Probability distribution of debris flow depth and its implication in risk assessment - Li, Yong; Su, Pengcheng; Liu, Jingjing (Italian journal of engineering geology and environment, 2011)
Debris flow moves in manner of successive surges and deposits by piling of surges. The surge occurs randomly and varies in properties and magnitude. This study explores the probability distribution of velocity and derives the distribution of flow depth based on observations in Jiangjia Gully in the southwest of China. The Weibull distribution is found to be well applicable to both the velocity and depth, with parameters varying in a rather small range. Therefore, the distribution is expected to hold in general for debris flows in different conditions and can be used to estimate the discharge of a potential debris flow. The estimated quantity is better than those inferred from the rainfall at a given frequency because it incorporates both the variation of surges and the real condition of the valley. In conclusion, The distribution provides a more reliable method of risk assessment of debris flow.